Transfer Pricing and Sourcing Strategies for Multinational Firms. (15th January 2014) - Shunko, Masha; Debo, Laurens; Gavirneni, Srinagesh
<x xml:space="preserve">Abstract</x> Taking advantage of low tax rates using transfer pricing and taking advantage of low production costs using offshoring are two strategies multinational firms (MNFs) use to increase profits. We identify an important trade‐off that MNFs face in setting their transfer prices: the conflict between (i) the incentive role and (ii) the tax role of the transfer price. For MNFs, we find the profit‐maximizing transfer‐pricing strategies that motivate divisional management to (i) make good sourcing decisions and (ii) take advantage of favorable tax rates. We quantify the absolute and relative maximum inefficiency in terms of the after‐tax MNF's profit change from using a single transfer‐pricing system as compared to the dual transfer‐pricing system. We show that the highest relative loss is attained when the average sourcing cost and the tax differential are high. We demonstrate that the highest absolute loss is attained when the average outsourcing cost is approximately equal to the offshoring cost. We extend our results to two practical variations in MNF structures: an MNF that faces operational constraints on its offshoring capacity and an MNF that uses compensation contracts linked to after‐tax firm‐wide profits. Our insights help MNFs' managers identify when to use single and dual transfer‐pricing systems.